Poised regeneration of zebrafish melanocytes involves direct differentiation and concurrent replenishment of tissue-resident progenitor cells - Iyengar, Sharanya (Dev Cell, 2015)
Efficient regeneration following injury is critical for maintaining tissue function and enabling organismal survival. Cells reconstituting damaged tissue are often generated from resident stem or progenitor cells or from cells that have dedifferentiated and become proliferative. While lineage-tracing studies have defined cellular sources of regeneration in many tissues, the process by which these cells execute the regenerative process is largely obscure. Here, we have identified tissue-resident progenitor cells that mediate regeneration of zebrafish stripe melanocytes and defined how these cells reconstitute pigmentation. Nearly all regeneration melanocytes arise through direct differentiation of progenitor cells. Wnt signaling is activated prior to differentiation, and inhibition of Wnt signaling impairs regeneration. Additional progenitors divide symmetrically to sustain the pool of progenitor cells. Combining direct differentiation with symmetric progenitor divisions may serve as a means to rapidly repair injured tissue while preserving the capacity to regenerate.